The effect of corruption on entrepreneurship in the presence of weak regulatory quality: Evidence from developing countries. (April 2023) - Abd Rashid, Suliza; Masron, Tajul Ariffin; Malim, Nurhafiza Abdul Kader
Abstract: Efforts to improve currently low entrepreneurship in developing countries could be necessary but likely hampered by the high corruption. With poor regulatory quality in most developing countries, the effect of corruption on entrepreneurship could be unique. By using the Generalized Method of Moments (GMM) estimator, utilizing 48 developing countries as the sample for the period from 2008 to 2016, this study finds that there is a conditional effect of corruption on entrepreneurship, implying that poor regulatory quality has forced and opened up the door for individuals to offer bribes in order to start a new business. Nonetheless, as corruption could add to the high cost of business start-ups, to enhance entrepreneurship, policymakers need to give priority to improving regulatory quality and, subsequently, force corruption to fade away. Highlights: With poor regulatory quality in most developing countries, the effect of corruption on entrepreneurship could be unique. Applying the GMM for 48 developing countries between 2008 and 2019, threshold effect of regulation on the corruption-entrepreneurship nexus is observed. To enhance entrepreneurship, policymakers need to give priority to improving regulatory quality and subsequently, to force corruption away.